Identifying Usability and Productivity Dimensions for Measuring the Success of Mobile Business Services - Maiju Vuolle; Anne Aula; Minna Kulju; Teija Vainio; Heli Wigelius (Advances in Human-Computer Interaction)
This paper reviews existing measures used for evaluating the usability of information systems and those used for evaluating the level of the productivity of a company. We discuss the usefulness of the existing measures in the mobile business context, where both mobility and work-context pose specific demands for the mobile business services. The review showed that the existing measures rarely consider the great contextual variation caused by the mobility of the services and the demands this poses on usability; which, in turn, affects productivity. To build a measurement tool that better meets the requirements of mobile business services, we completed case studies on two mobile business services, one used in passenger transport and the other in construction sites. Based on the understanding gained from the case studies, we propose a list of dimensions and items addressing both usability and productivity aspects that work as the basis for a multidisciplinary measurement tool.